COVID anxiety and its predictors among Slovak adolescents - Jozefiakova, Bibiána; Kascakova, Natália; Furstova, Jana; Sarnikova, Gabriela; Hasto, Jozef; Tavel, Peter (Frontiers in Psychology, 2022)
The Covid-19 pandemic and its related restrictions, mainly social distancing, had an impact on the mental health of various groups, including adolescents. The main goal of our study was to explore the impact of gender, age, resilience (measured using the Brief Resilience Scale), attachment anxiety, attachment avoidance (both measured using the Experiences in Close Relationships Revised Scale for adolescents), and mental and general health (measured using items of SF-8 Health Survey) on Covid anxiety (measured using the Covid Anxiety Scale) among a sample of Slovak adolescents (N=1786, age 15 to 19, mean age=16.8, SD=1.2). The data were collected online between 13 April and 24 May 2021. Four nested linear regression models were fitted to the data and evaluated. The significant predictors that had a greater effect than our smallest effect size of interest (SESOI) (β = 0.10) were gender (β=-0.26, p<0.001, where boys had lower scores in Covid anxiety), general and mental health (β=-0.13 and β=-0.14, respectively, both with p<0.001), resilience (β=-0.12, p<0.001), and attachment avoidance (β=-0.11, p<0.001). Similarly, age and attachment anxiety were significant predictors with a lower effect size (β=0.06, p=0.003, and β=0.09, p<0.001, respectively). Our results are in line with previous research findings highlighting the importance of prevention and interventions programmes focused mainly on preventing loneliness and social disconnection, fostering secure attachment with parents and peers, and increasing the resilience of adolescents, especially in the stressful time of a pandemic, to promote their mental health.